Determination of the heavy metals contamination from batik factory effluents to its surrounding - Muslim, Noor Zuhartini Md (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2016)
Batik industries may produce a large amount of effluents with a high concentration of pollutants such as heavy metals. Heavy metals are environmentally stable, non-biodegradable, and toxic to living beings. Heavy metals tend to accumulate in soils, plants and eventually cause chronic and adverse effects on human health. In this study, the levels of heavy metals in effluent, soil and plant around batik factories were determined using atomic absorption spectrophotometer (AAS). Effluent, soil and plant samples were collected from three batik factories in Kota Bharu , Kelantan. Cadmium (Cd), lead (Pb), zinc (Zn), copper (Cu), chromium (Cr), and iron (Fe) were chosen as representative metal elements. The results indicated that high concentration of heavy.